Intimate Partner Violence and Completion of Post-Sexual Assault Medical Forensic Examination Follow-Up Screening - Gilmore, Amanda K. (Journal of interpersonal violence, 2021)
Sexual assault is a major public health concern associated with significant mental health and medical symptoms. Follow-up screening post-sexual assault medical forensic examination (SAMFE) can be one method of determining needs and providing targeted prevention of mental health and medical symptoms among individuals who experienced a recent sexual assault. However, the factors associated with engagement in post-SAMFE follow-up screening have not been identified. The current study examined the association between intimate partner violence victimization and sexual assault–related characteristics and engagement in post-SAMFE follow-up screening. Participants were 193 individuals who received a SAMFE and indicated at the time of SAMFE that they were interested in follow-up by the hospital. It was found that individuals were less likely to engage in follow-up screening if the assault was perpetrated by an intimate partner. These findings suggest that other resources are needed to reach individuals who experience sexual assault perpetrated by an intimate partner due to the unique needs of that population.